The Interplay of Ubuntu and Hospitality as Defining Tenets in African and South African Ethics: A Christian Ethics Reflection (Global Journal of Human-Social Science, 2022)
The notion of Ubuntu as a moral theory in the South African and African contexts presents attractive norms of an African world view that can be articulated and applied to contemporary Christian ethics The proponents of Ubuntu perceive it as an African philosophy based on the maxim a person is a person through other persons whereby the community prevails over individual considerations It is not merely an empirical claim that our survival or well-being is causally dependent on others but is in essence capturing a normative account of what we ought to most value in life The shortcomings of Ubuntu should not preclude from reflecting on Ubuntu as a natural ethic potential that enforces and engenders hospitality neighbourliness and care for all humanity In this instance Ubuntu should shift to liminal Ubuntu with Christ as a bond as Ubuntu seeks to restore African communal cultural behaviours Hospitality should be practiced by doing or reflecting on things which might look insignificant such as supporting the vulnerable the marginalized and the migrants that come to South Africa from the neighbouring African countries that bear the brunt of xenophobic acts This article seeks to appeal to the predominant influence of Ubuntu and Judeo-Christian ethos embedded in the South African psyche to the challenge posed by xenophobia The article further argues for human dignity as understood by identifying and exhibiting solidarity with others